The Validity of The Student Worksheet of Thermal Energy Material Based on Science, Technology, Engineering, Mathematics (STEM) and Local Wisdom to Enhance Scientific Literacy - Maula Ariefianti; Arif Sholahuddin; Mustika Wati (Universitas Lambung Mangkurat, 2023)
Scientific literacy is one of the primary objectives of scientific education. Despite this, field research indicates that scientific literacy remains inadequate. The approach of Science, Technology, Engineering, and Mathematics (STEM) and local wisdom have scientifically obtained substantive supports in addressing comparable challenges. However, the STEM-based Learner Worksheet and the incorporation of local wisdom into scientific education remain underdeveloped. The purpose of this research is to describe the validity of thermal energy worksheet based on STEM and local wisdom in enhancing scientific literacy. This research and development employed the Borg and Gall model. The validation sheet used to acquire the worksheet validation data were reviewed by two practitioners and three experts. The validation data was derived by averaging the validator's scores on all assessment components, with the calculation outcomes being modified to adhere to the validity criteria. The results indicated that the validity of the worksheet based on STEM and local wisdom of thermal energy material was classified as very valid with an average score of 3.49. Therefore, the worksheet based on STEM and local wisdom regarding thermal energy materials are deemed valid and can be implemented in the subsequent phase of classroom trials.